Ghrelins, obestatin, nesfatin-1 and leptin levels in pregnant women with and without hyperemesis gravidarum - Gungor, Sami; Gurates, Bilgin; Aydin, Suleyman; Sahin, Ibrahim; Kavak, Salih Burcin; Kumru, Selahattin; Ozdemir, Nazan (Pergamon-Elsevier Science Ltd, 2013)
Objectives: The goal of this study was to compare levels of acyl and des-acyl ghrelin, obestatin, nesfatin-1 and leptin in healthy gravidas to hyperemesis gravidarum (HG) patients. Design and methods: Twenty pregnant women with HG and twenty healthy pregnant women all of similar ages, BMI and all at similar pregnancy development comprised the study cohort. Fasting serum samples were obtained and measured for acyl and des-acyl ghrelin, leptin, obestatin and nesfatin-1. Results: Nesfatin-1 concentrations in the HG group were higher compared to the control group whereas; leptin concentrations during pregnancy were lower in the HG group as compared to the control group. The two groups did not differ with regard to acyl and des-acyl ghrelin and obestatin. Conclusion: This pilot study suggests a possible role of leptin and nesfatin-1, which might be involved in the pathology of the disease. (C) 2013 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Hyperemesis gravidarum; Ghrelin; Obestatin; Leptin; Nesfatin-1